Microplastic pollution in seawater and marine organisms across the Tropical Eastern Pacific and Galápagos - Alonzo Alfaro-Núñez (Nature Portfolio, 2021)
Abstract Detection of plastic debris degrading into micro particles across all oceanic environments and inside of marine organisms is no longer surprising news. Microplastic contamination now appears as one of the world’s environmental main concerns. To determine the levels of microplastic pollution at sea, water samples were collected across a 4000 km-trajectory in the Tropical Eastern Pacific and the Galápagos archipelago, covering an area of 453,000 square kilometres. Furthermore, 240 specimens of 16 different species of fish, squid, and shrimp, all of human consumption, were collected along the continental coast. Microplastic particles were found in 100% of the water samples and marine organisms. Microplastic particles ranging from 150 to 500 µm in size were the most predominant. This is one of the first reports simultaneously detecting and quantifying microplastic particles abundance and their impact on marine organisms of this region.